Sport-Specific Agility and Change of Direction in Water Polo: The Reliability and Validity of Two Newly Developed Tests. (18th December 2021) - Dong, Lily; Paradelo, David; Delorme, Alain; Oliveira, Justin; Parillo, Brian; Croteau, Félix; Romeas, Thomas; Dubé, Evelyne; Bieuzen, François; Billaut, François; Berryman, Nicolas
Abstract: Dong, L, Paradelo, D, Delorme, A, Oliveira, J, Parillo, B, Croteau, F, Romeas, T, Dubé, E, Bieuzen, F, Billaut, F, and Berryman, N. Sport-specific agility and change of direction in water polo: The reliability and validity of two newly developed tests. J Strength Cond Res 35(12S): S111–S118, 2021—There is a gap in water-based agility testing that considers both the change-of-direction (COD) and perceptive-reactive components of agility. This study sought to develop easily implementable, sport-specific in-water agility tests for water polo and to verify the reliability and validity of these new tests: the in-water Stop and Go (SG) and Jump and Go (JG). Female water polo athletes at the Senior ( n = 12, age = 22.1 ± 2.1 years), Junior ( n = 19, age = 18.5 ± 1.0 years), and Youth ( n = 11, age = 16.5 ± 0.8 years) national levels performed 3 trials of each of the SG, JG, and the existing Functional Test for Agility Performance (FTAP). Senior athletes performed an additional experimental session to assess reliability parameters. Relative reliability for agility and COD versions of the SG and JG was high or very high (intraclass correlation coefficient [ICC] = 0.76–0.95). For construct validity analyses, significant between-group differences for each of the new tests ( p < 0.05) were found. In contrast, the FTAP was moderately reliable (ICC = 0.57) and was unsuccessful in discriminating between playing levels. Considering the favorable metrological properties of the SG and JG, their fidelity to in-game demands, and their accessible setups, these new tests represent viable options to implement at grassroots and elite levels for the assessment and training of water polo–specific agility.